Spontaneous bilateral femoral neck and left scapula fracture in a young adult with end-stage renal disease - Kaur, Amninder; Saini, Sandeep; Cheluvaiah, Chandra S.; Dhoot, Dipesh K.; Koley, Himadri (International Journal of Research in Medical Sciences, 2022)
Renal osteodystrophy is not uncommon in chronic kidney disease patients however fractures are not common among these patients. Bilateral spontaneous femoral and scapular fractures due to renal osteodystrophy are extremely uncommon. We report a case of spontaneous bilateral femoral neck fracture and left scapular neck fracture associated with secondary hyperparathyroidism in a patient of end-stage renal disease.